Sex and Marriage in the Sentences of Peter Lombard - Finn, Thomas M. (Theological studies, 2011)
Scholastic theology first saw the light of day among the masters in the twelfth-century schools of Europe. Chief among the masters of theology was Peter Lombard, whose Sentences became the textbook in the universities of Europe until the 16th century. This article studies the theology of sex and marriage in Book 4 of the Sentences against the background of the long and difficult road marriage travelled from a familial and secular event to the sacramental world of the church.